Pengembangan Video Ajar Kalkulus Integral Berbasis Pen Tablet Di Universitas Pasir Pengaraian - Isharyadi, Ratri; Annajmi, Annajmi (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2022)
This research aims to produce a practical and valid video for learning integral calculus using a pen tablet. This type of study is known as development research. This study employs a three-dimensional development model, consisting of define, design, and development. The research instrument consisted of a questionnaire completed by material experts and media experts to assess the video’s validity and a questionnaire completed by students to assess the video’s usability. Based on the stages of development that have been completed, it can be concluded that the resulting instructional video is valid. According to the validation results, both material experts and media experts have a very high level of validity, with a total average score of 3.72 and 3.77, respectively. Videos created with a pen tablet are also useful videos. According to the criteria used to determine the usefulness of instructional videos, the overall average is 80.88 percent. This demonstrates that the practicality of pen tablet-based integral calculus instructional videos is very good. The findings indicate that the instructional videos created can be utilized in the learning process.